Effects of Urea and Imazethapyr on Orobanche Crenata germination, Radicle extension, Incidence and Faba Bean Growth and Yield - A. Abdel-Daim, Sawsan; Gadir, Abdel; H. Eltayeb, Amani; M. Abusin, Rashida; T. Babiker, A. G. (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Orobanche crenata Forsk., a debilitating root parasitic weed, has become an important constraint to production of cool season legumes in Sudan. The present investigation was undertaken to determine the effects of urea, the herbicide imazethapyr and their combinations on the parasite germination, radicle extension, incidence and faba bean growth and yield. The results showed that urea at 20-400 mM reduced O. crenata seeds germination and radicle extension in a concentration dependent manner. Imazethapyr did not reduce germination and effected inconsistent reductions in radicle length. Unrestricted parasite growth had no significant adverse effects on number of faba beans leaves and plant height. However, it reduced the number of pods by 20.2 and 38.8% and grain yield by 35.3 and 46.9%. Imazethapyr at 47.6 g a.i. ha-1 applied 45, 30, 15 days, subsequent to and at sowing, suppressed O. crenata emergence by 22.7, 94.3, 94.8 and 67.7% early in the season. However, late in the season only poor to moderate control was achieved. The corresponding figures for the high rate (71.4 g a.i. ha-1) were 72.4, 97.6, 97.4 and 96.8%. However, late in the season only poor (39%) to satisfactory (69%) control was achieved. Urea, alone, effected poor control (20-43.5%) and when applied to the herbicide treated sub-plots did not inflict further reductions. however, capsules production was reduced by 43-85%. The herbicide alone increased grain yield by 24-79%. The combination herbicide and urea at sowing increased yield by 87.5-111.4%. Contrary to the general belief that O. crenata inflicts most of its damage during the subterranean phase the results suggest that in irrigated faba beans most of the damage is synchronized with the parasite emergence.